Imaging Informatics: 25 Years of Progress - Agrawal, J. P.; Erickson, B. J.; Kahn, C. E., Jr. (Yearbook of Medical Informatics, 2016)
The science and applications of informatics in medical imaging have advanced dramatically in the past 25 years. This article provides a selective overview of key developments in medical imaging informatics. Advances in standards and technologies for compression and transmission of digital images have enabled Picture Archiving and Communications Systems (PACS) and teleradiology. Research in speech recognition, structured reporting, ontologies, and natural language processing has improved the ability to generate and analyze the reports of imaging procedures. Informatics has provided tools to address workflow and ergonomic issues engendered by the growing volume of medical image information. Research in computer-aided detection and diagnosis of abnormalities in medical images has opened new avenues to improve patient care. The growing number of medical-imaging examinations and their large volumes of information create a natural platform for “big data“ analytics, particularly when joined with high-dimensional genomic data. Radiogenomics investigates relationships between a disease’s genetic and gene-expression characteristics and its imaging phenotype; this emerging field promises to help us better understand disease biology, prognosis, and treatment options. The next 25 years offer remarkable opportunities for informatics and medical imaging together to lead to further advances in both disciplines and to improve health.
Keywords: Diagnostic imaging; radiology information systems; decision support systems; clinical; image interpretation; computer-assisted; medical informatics